Comparative Analysis of Long Non-Coding RNA Expression and Immune Response in Mild and Severe COVID-19 - Zhang, Yongting; Shi, Fan; Wang, Yuchong; Meng, Yuting; Zhang, Qiong; Wang, Kaihang; Zeng, Ping; Diao, Hongyan (Frontiers in Molecular Biosciences, 2022)
Background Coronavirus disease 2019 (COVID-19) is a worldwide emergency, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Long non-coding RNAs (lncRNAs) do not encode proteins, but could participate in immune response. Methods In our study, 39 COVID-19 patients were enrolled. Microarray of peripheral blood mononuclear cells (PBMCs), from healthy and COVID-19 patients, was applied to identify the expression profiles of lncRNAs and mRNAs. Identified differentially expressed (DE) lncRNAs in COVID-19 were validated by qRT-PCR. Then the enrichment of DE mRNAs, related to lncRNAs, were analyzed through Metascape. The difference in frequencies of immune cells and cytokines were detected by CIBERSORT and ImmPort. Results All patients with COVID-19 displayed lymphopenia, especially in T cells, and hyper-inflammatory responses, including IL-6 and TNF-α. Four immune related lncRNAs in COVID-19 were found and further validated, including: AC136475.9，CATG00000032642.1, G004246, XLOC_013290. Functional analysis about lncRNAs suggested that they negatively correlated with antigen processing and presentation and T cell receptor, but positively correlated with apoptosis, which contributed to lymphopenia, especially T cell cytopenia. In addition, they were positively related to monocyte expansion, and accumulation of cytokines and chemokines, then exacerbated the COVID-19. Conclusion Taken together, four COVID-19 lncRNAs were correlated with the T cells cytopenia by potentially affecting the antigen processing and presentation, T cell receptor signaling pathway, and apoptosis; and monocyte expansion through cytokines and chemokines.